Overload blunts baroreflex only in overreached athletes. Issue 9 (September 2018) - Bourdillon, Nicolas; Yazdani, Sasan; Nilchian, Masih; Mariano, Alessio; Vesin, Jean-Marc; Millet, Grégoire P.
Abstract: Objectives: Heart rate variability (HRV) is commonly used to diagnose overreaching and monitor athletes' responses to training. Baroreflex sensitivity (BRS) is modified by changes in training load and might be another means to detect overreaching. The goal of this study was to assess BRS and HRV changes in two groups of athletes responding either negatively (FOR) or positively (AF) to similar training overload. Design: Fifteen athletes performed 2-week baseline (BSL) training followed by 3-week overload (+45%; OVL) and 2-week recovery (−20%; RCV). Methods: HRV, training load and subjective fatigue were measured daily via questionnaires. BRS, salivary cortisol and testosterone, and submaximal exercise and maximal 3-km run performances were measured at the end of each period. Results: Based on their performance change during OVL, 8 athletes were diagnosed as FOR and 7 as AF. Subjective fatigue was increased in FOR athletes during OVL. BRS increased in AF but not in FOR athletes during RCV. At the end of RCV, cortisol and testosterone were higher than BSL in both groups. Conclusions: Three weeks of similar training overload can induce either performance enhancement or overreaching. The changes in submaximal exercise and maximal performances and in subjective fatigue were the fastest-responding parameters that distinguished the two groups of athletes during OVL. Training overload blunted the increase in BRS in FOR only. Most of the differences in BRS were observed during the recovery period. BRS appears to be a more sensitive parameter than HRV for early monitoring of responses to training.